Decolonizing spaces: A (visual) essay on strategies of appropriation, transformation and negotiation of the colonial built environment in postcolonial Congo - Lagae, Johan; Beeckmans, Luce; Boonen, Sofie (Hagar: Studies in Society and Culture, 2010)
This paper starts from the assumption that the current physical landscape in the Democratic Republic of the Congo can be read as a territorial palimpsest which testifies to a continuing process of layering uses and meanings, a process that occurred during colonial times but is still ongoing today. Through a series of case studies, each of which is introduced by a recent photograph taken by the authors, we aim to decode particular colonial spaces in the DRC and show how they were (re)constructed and shaped over time and thus became "decolonized." In doing so, the analysis touches on issues of both (post)colonial history and memory. A wide variety of typologies of former colonial spaces has been chosen, from buildings to urban spaces, and from privately owned sites to more official institutions, located in cities like Kinshasa and Lubumbashi, as well as in the region of the Lower Congo. As such, the series presented here illustrates a number of strategies of appropriation, transformation and negotiation of colonial built legacy that are indicative of both official policies of (re)use and informal practices of everyday survival.